Daniel S. Markey, No Exit from Pakistan: America’s Tortured Relationship with Islamabad - Mr. Majid Mahmood (CISS Insight Journal, 2014)
In No Exit from Pakistan: America’s Tortured Relationship with Islamabad Daniel S. Markey argues that Pakistan has often been a hostile and difficult partner for United States to manage. In his opinion, however, despite several setbacks and failures in the bilateral relationship neither Pakistan nor the United States can afford a permanent breakup. Markey maintains that there are immediate, vital and emergent threats emanating from Pakistan that will have a negative impact on US’ regional interests in South Asia, Central Asia and Middle East. It is due to this reason the author, contrary to what many experts and officials may feel in Washington, argues that the United States cannot afford to disengage from Pakistan. The term “No Exit” in the title of the book borrowed from an old WWII French play Huis Clos is meant to convey this sense of compulsive engagement. Daniel Markey methodically surveys Pakistan – US relations disaggregated at three levels of domestic, regional and international politics. As a result the reader easily grasps the arguments presented in the book. Markey has linked all his arguments on these three levels with broader US interests in the region in a manner that they truly reflect his all – inclusive understanding of Pakistan and US policy objectives in the region.